Sosialisasi Kesehatan Reproduksi Sebagai Upaya Peningkatan Lifestyle Remaja Yang Sehat dan Unggul Di Desa Tuah Mesade - Halimatussakdiyah Lubis; Fika Lestari (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Period most vulnerable to experiencing reproductive health problems such as early pregnancy, unsafe abortion which can cause the death of mother and child, depression, sexually transmitted infections (STIs) such as Human Immunodeficiency Virus (HIV), sexual harassment, infertility, and malignancies such as cervical cancer. Adolescents begin to focus on behavior that is associated with adult status, namely smoking, drinking alcohol, using drugs, and engaging in promiscuous sexual acts which are quite disturbing. Community Service "Reproductive Health Socialization as an Effort to Improve the Healthy and Excellent Lifestyle of Adolescents in Tuah Mesade Village was held on 9-11 February 2024 with a total of 30 participants. Socialization is provided by the community service team regarding the introduction of male and female reproductive organs, how to care for reproductive organs, nutrition in reproductive health, and sexually transmitted infections. The extension participants seemed enthusiastic about the materials presented by the resource persons and were able to be actively involved, so this extension activity took place in a two-way system and many participants asked questions. The presentation of the counseling material was followed by discussion, ice breaking, and distribution of door prizes in the form of a book with the title "Teaching Book on Nutrition in Reproductive Health" to participants who were active during the discussion activities.